Estimasi Potensi dan Kinerja Sapi Bali di Kabupaten Timor Tengah Utara, Propinsi Nusa Tenggara Timur (The Potency Estimation and Performance of Bali Cattle in Timor Tengah Utara Regency, East Nusa Tenggara Province) - Trimeldus Tulak Tonbesi; Nono Ngadiyono; Sumadi (Sumadi) (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
The objective of the reseaech was to recognize the output and population dynamics, correlation between body weight and body size, and also correlation between body weight and carcass weight and the most accurate body weightestimation on Bali cattle in Timor Tengah Utara Regency, East Nusa Tenggara Province. This research was done in 6 districts in 20 villages. The research material included 289 breeders as respondent, 530 Bali cattles and secondary datafrom local Department of Animal Husbandry. The results showed that reproduction efficiency 83.60%, 21.72% natural increase, 21.47% potency of the population or 16,204 animals. There was annual increased with average 8.16% followsregression equation Y = 63,151+5,376 X and by year of 2011 the population could be estimated as many as 100,783 animals with potency 21,638 animals. Correlation between body weight with body size in male Bali cow age >1 to 2years old followed equation Y = -286.13+2.11 X1+1.59X4 with r = 0.92 and R2 = 0.85. Male with age >2 to 3 years old, Y = -441.16+2.23X1+2.96X3 with r = 0.95 and R2 = 0.90. Female age >2 to 3 years old, Y = -153.27+2.19X1 with r =0.78 and R2 = 0.60. Male with age >3 to 4 years old, Y = -385.10+4.13X1 with r = 0.96 and R2 = 0.91. Female age >3 to 4 years old, Y = 89.72+0.96X2 with r = 0.34 and R2 = 0.12. Correlation between body weight and carcass weight infemale age >2 to 3 years old, Y = -3.84+0.56X with r = 0.97 and R2 = 0.94, female age >3 to 4 years old, Y = 4.0+1.50X with r = 0.87 and R2 = 0.76, and female age >4 years old, Y = 3.16+0.52X with r = 0.96 and R2 = 0.92.Djagra Formula could be used to estimate male and female Bali cattle body weight in regency north middle Timor with correction factor each -0.34% and -16.71%.(Key words: Bali Cattle, Performance, Potency, Population dynamics)